ANALISIS VARIASI PENGGUNAAN BAHASA PADA MEDIA SOSIAL INSTAGRAM: KAJIAN SOSIOLINGUISTIK - Azzahra, Fitri Aulia; Djumingin, Sulastriningsih; Saleh, Muhammad (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2024)
This study is a quantitative research that aims to describe the variation of language use on Instagram social media and to describe the causes of the variation. This research uses qualitative research method with descriptive method. The data collection techniques are documentation and note-taking techniques. The results of this study show that there are six types of language variation on Instagram social media, namely language variation in terms of speakers, language variation in terms of usage, language variation in terms of formality, language variation in terms of means, slang variation, and mixed Indonesian-English language variation. In addition, in this study there are factors that cause the use of language variation on Instagram social media. The new finding in this research is the form of data analysis made in the form of a formula as part of data grouping. Slang and mixed language variations in Instagram social media become a renewable form in this research, showing the diversity of language forms that have different meanings or meanings in each word found.